A Comprehensive Study on the Scientific Literatures Performance of Cash Waqf Linked Sukuk (CWLS) using NVivo - Aam Slamet Rusydiana; Nadia Nurul Izza (SMART Insight, 2023)
This study seeks to map research related to Cash Waqf Linked Sukuk (CWLS) published by Dimensions indexed journals from 2019 to 2023. NVivo 12 Plus is used to conduct thematic studies and the frequency is used to evaluate 53 publications in scientific literature. The results of the study found that the number of publications fluctuated from year to year related to CWLS research which indicated that this topic was an interesting topic and should continue to be developed. In addition, various focus discussions and cluster analysis that describe research paths in CWLS Waqf research include economic empowerment, CWLS as productive waqf, social investment, and CWLS research methods. According to the exploratory review and visualization in the cluster analysis, CWLS research includes CWLS Waqf including economic empowerment, CWLS as productive waqf, social investment. This research can be used as a starting point for experts to build graphic visualizations of CWLS research patterns in published scientific research.